Pengaruh Pembiayaan Murabahah Terhadap Perkembangan UMKM di Kecamatan Ngoro - Asipah, Ainun; Fahrullah (Jurnal Ekonomika dan Bisnis Islam, 2020)
This study aims to find out how much the influence of murabahah financing on the development of UMKM in Ngoro. This study illustrates quantitative research using a descriptive approach. The data used by researchers are primary interviews and secondary data in the form of customer data reports that have received murabahah financing from PT. BPRS Mojokerto City, Ngoro Jombang branch. For the population and sample of researchers using secondary data in the form of customer data reports that have received murabahah financing from PT. BPRS Kota Mojokerto branch of Ngoro Jombang. The analysis technique used is simple linear regression. The results of this study state that the partial test (t) states that murabahah financing significantly influences the development of UMKM in Ngoro District. The test results of the coefficient of determination (R2) indicate that the effect of murabahah financing affects the development of UMKM in Ngoro District worth 93%, while the remaining 7% is influenced by other variables not examined.